2021
DOI: 10.3389/fgwh.2021.599731
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Service Delivery? The Impact of Conflict on Antenatal Care Quality in Kenya

Abstract: Introduction: African countries facing conflict have higher levels of maternal mortality. Understanding the gaps in the utilization of high-quality maternal health care is essential to improving maternal survival in these states. Few studies have estimated the impact of conflict on the quality of health care. In this study, we estimated the impact of conflict on the quality of health care in Kenya, a country with multiple overlapping conflicts and significant disparities in maternal survival.Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…That may be because of inequalities in access to ANC services and the views of populations about the importance of ANC 25. Moreover, in some of the East African countries, there is ongoing conflict and persistent political instability that played an important role in hindering the quality of the ANC; the scholars revealed that lack of safety played a major role in reducing the ANC, especially in remote areas 26 27…”
Section: Discussionmentioning
confidence: 99%
“…That may be because of inequalities in access to ANC services and the views of populations about the importance of ANC 25. Moreover, in some of the East African countries, there is ongoing conflict and persistent political instability that played an important role in hindering the quality of the ANC; the scholars revealed that lack of safety played a major role in reducing the ANC, especially in remote areas 26 27…”
Section: Discussionmentioning
confidence: 99%
“…Of the twenty-one included studies, seventeen (81.0%) reported healthcareseeking behaviors for maternal health services in settings of armed violent conflict. The reported healthcare-seeking behaviors were antenatal care attendance, skilled birth attendance, postnatal care services, family planning uptake/contraceptive prevalence rate, health facility birth, caesarean section rates, unmet need for family planning, and HIV/AIDs care and treatment [19,20,39,41,45,47,[50][51][52][53][54][55][56][57][58][59][60]. Nine studies (42.9%) reported healthcare-seeking behaviors for child health.…”
Section: Search Resultsmentioning
confidence: 99%
“…Healthcare services and their quality were negatively affected by factors such as insufficient financing, shortage of healthcare personnel, and destruction of infrastructure [20,58]. Poor quality of healthcare services as well as past unpleasant experiences in health facilities, contributed to a lower demand for maternal healthcare usage [45,50,51]. Male partner's attitudes or their negative perceptions of healthcare services emerged as significant barriers to positive health-seeking behavior [45,55,57,60].…”
Section: Insert Here…mentioning
confidence: 99%
“…As similar studies indicated that without further efforts in the rural and poorest areas, where the majority of maternal mortality is reported, Ethiopia's effort to achieve the 2030 SDGs could be hindered [20]. In addition, as evidenced by other studies in Kenya, threatening factors, like the current COVID‐19 pandemic [40], and some unrest and conflicts in some parts of the country could worsen and disrupt the appropriate delivery of maternal health‐care services and sustain a woman's LTR disparities in maternal mortality [41].…”
Section: Discussionmentioning
confidence: 99%